1970
DOI: 10.22278/2318-2660.1984.v11.n2/3.a917
|View full text |Cite
|
Sign up to set email alerts
|

Poluição por Cádmio e lesão renal em habitantes de Santo Amaro da purificação, Bahia

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the meantime, three new studies were carried out by the PEER Group: the first published in 1995, with cattle grazing on Plumbum's premises, revealed that the rates of chromosomal alterations were higher among animals from Santo Amaro (5.6%) than among control animals (0.3%), while the mean lead level in Santo Amaro cattle was 24.4 µg/dl and 1.7 µg/dl among control animals; the second study showed high concentrations of lead, cadmium and organochlorides in sediments and molluscs from the entire ecosystem north of Todos os Santos Bay (TAVARES 1996); and the third in 1998, in children exposed to slag stirred up from the sub-base of the paving the Ruy Barbosa Street, in Santo Amaro, when they were opened for the implementation of the Bahia Azul Project, an environmental sanitation program for Salvador and the cities surrounding the TSB found that the mean level and the respective standard deviation of the children's PbS was 17.1±7.34 µg/dl (CARVALHO et al 2001) In December 1998, the Department of Mining Engineering at the Polytechnic School of the University of São Paulo (PMI) concluded the first investigation on the toxicity and contamination routes resulting from the leaching of slag on the Plumbum's premises (soil, surface, and groundwater ), the main geochemical processes and physical-chemical parameters responsible for the retention or availability of metals, as well as a proposal for a remediation and monitoring technique for the area.…”
Section: The Plumbum Co Environmental Liabilitiesmentioning
confidence: 99%
“…In the meantime, three new studies were carried out by the PEER Group: the first published in 1995, with cattle grazing on Plumbum's premises, revealed that the rates of chromosomal alterations were higher among animals from Santo Amaro (5.6%) than among control animals (0.3%), while the mean lead level in Santo Amaro cattle was 24.4 µg/dl and 1.7 µg/dl among control animals; the second study showed high concentrations of lead, cadmium and organochlorides in sediments and molluscs from the entire ecosystem north of Todos os Santos Bay (TAVARES 1996); and the third in 1998, in children exposed to slag stirred up from the sub-base of the paving the Ruy Barbosa Street, in Santo Amaro, when they were opened for the implementation of the Bahia Azul Project, an environmental sanitation program for Salvador and the cities surrounding the TSB found that the mean level and the respective standard deviation of the children's PbS was 17.1±7.34 µg/dl (CARVALHO et al 2001) In December 1998, the Department of Mining Engineering at the Polytechnic School of the University of São Paulo (PMI) concluded the first investigation on the toxicity and contamination routes resulting from the leaching of slag on the Plumbum's premises (soil, surface, and groundwater ), the main geochemical processes and physical-chemical parameters responsible for the retention or availability of metals, as well as a proposal for a remediation and monitoring technique for the area.…”
Section: The Plumbum Co Environmental Liabilitiesmentioning
confidence: 99%
“…This smelter used the classical sinterroasting process followed by smelting and refining (de Andrade Bernardez 2010, 2011a, b;Habashi 2002). Many studies indicate that people living near this smelter were affected by potentially toxic elements, especially Pb and Cd (Mendes 1977;Loureiro et al 1983;Tavares et al 1983Tavares et al , 1989Carvalho et al 1984aCarvalho et al , b, c, 1985Carvalho et al , 1986Carvalho et al , 1989aCarvalho et al , b, 1995Carvalho et al , 1996Carvalho et al , 1997Carvalho et al , 2003, 1987Tavares and Carvalho 1992). An epidemiological survey of children born after the lead smelter closedown and living near the smelter indicates persistently high blood Pb levels (Carvalho et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Em face do ocorrido, o CRA notificou a referida empresa para requerer o licenciamento ambiental.O parecer técnico 055/95-SFA/CRA determinou que a fabrica de guardanapos Boka Loka, não poderia iniciar operação, antes que fossem adotadas as exigências ambientais previstas na Legislação Ambiental do Estado da Bahia e a implantação do Plano de disposição final da escória pela Plumbum. BTS, constatou que o nível médio e o respectivo desvio padrão do PbS das crianças foi de 17,17,34 g/dl(CARVALHO et al 2001) Em dezembro de 1998 foi concluído no Departamento de Engenharia de Minas da O PDU de Santo Amaro foi a primeira tentativa de avaliar o solo contaminado de toda a cidade. Por meio de 10 amostras de solo coletadas em diferentes ruas foram analisadas as concentrações de chumbo total e seus resultados comparados com as concentrações utilizadas na Europa para multifuncionalidade do solo.…”
unclassified